Using Metabolic Engineering to Connect Molecular Biology Techniques to Societal Challenges - Gordy, Claire L.; Goller, Carlos C. (Frontiers in Microbiology, 2020)
In most biology courses, genetically modified organisms (GMOs) are discussed in the context of introducing a single protein-coding gene to produce a desired trait. We have developed a laboratory module for undergraduate and graduate students that builds upon students’ basic understanding of GMOs to introduce them to techniques used to sustainably produce commercially-valuable products in yeast through metabolic engineering. Students use recombination-based methods to assemble genes encoding entire metabolic pathways in Saccharomyces cerevisiae, perform genetic screens to identify yeast genes that impact metabolite yield, and use error-prone PCR to optimize metabolic pathway function. In parallel, students engage with the societal impact of these approaches through case studies of products made via yeast metabolic engineering, such as opioids, omega-3 fatty acids, and the Impossible Burger. In this report, we focus on these case studies as well as an individual sustainability project assignment created for this course. This assignment, which spans the 8-week module, asks students to find examples of yeast metabolic engineering that could be used to address current sustainability challenges in their communities. Student approaches to this project have varied from literature reviews, to news searches, to directly contacting and interviewing researchers using novel metabolic engineering approaches. These student-produced projects are used as case studies in future semesters, amplifying student voices and contributing to student ownership. While developed in the context of this course, the sustainability project and case studies are broadly applicable and could be adapted for use in biology or bioethics courses at the undergraduate or graduate level.